The Relationship Between Depression, Autoimmune Diseases and The Role of Exercise - A Literature Review - Woźniak, Julia; Kapturska, Natalia; Cymerys, Kinga; Kadłubek, Sabina; Sikora, Dominik; Góralczyk, Ewa; Kalinowski, Szymon; Mąka, Magdalena; Kardaszewski, Piotr; Rusek-Łajczak, Magdalena (Quality in Sport, 2026)
Introduction and purpose: Epidemiological evidence suggests a strong bidirectional relationship between depression and autoimmune diseases. The purpose of this review is to examine the shared neuroimmunological mechanisms linking these conditions and to evaluate the therapeutic role of physical exercise along with its clinical implications. Materials and methods: Medical databases such as PubMed, Google Scholar were searched, data analyzed and put into the single article. Description of knowledge: The gut-brain axis, vagus nerve signaling, and intestinal microbiota mediate the complex interactions between psychological and immunological processes. Dysregulation of the HPA axis, elevated pro-inflammatory cytokines (IL-6, TNF-α), and intestinal barrier dysfunction underlie both depression and autoimmune diseases like rheumatoid arthritis or inflammatory bowel disease. Physical exercise acts as a crucial modulator of these pathways, improving mood, functional capacity and lowering disease activity. Conclusion: Recognition of shared neuroimmunological pathways highlights the need for integrated therapeutic strategies. Physical exercise should be implemented as a key non-pharmacological treatment that reduces depressive and autoimmune symptoms. Combining targeted physical activity with psychobiotics, anti-inflammatory diets along with pharmacological treatment, provides a comprehensive, patient-centered approach necessary for improving clinical outcomes.